Tissue changes of extraction sockets in humans: a comparison of spontaneous healing vs. ridge preservation with secondary soft tissue healing. Issue 11 (12th July 2012) - Barone, Antonio; Ricci, Massimiliano; Tonelli, Paolo; Santini, Stefano; Covani, Ugo
Abstract Introduction As a consequence of extraction, the height of the buccal wall tends to decrease and results in the disappearance of bundle bone. To modify bone remodelling after extraction, various ridge preservation techniques have been proposed. The present research was drawn up with the following considerations in mind: to evaluate and to compare changes of hard and soft tissues in post‐extraction sockets which received a ridge preservation procedure, with post‐extraction sockets which had healed naturally. Materials and methods Each patient was randomly allocated to a test or control group using a specific software package. After extraction, the sockets were carefully inspected and any granulation tissue was removed. The control sites received silk sutures to stabilize the clot without any grafting material. The test sites were grafted with corticocancellous porcine bone and a collagen membrane. All experimental sites had the membranes left exposed to the oral cavity with a secondary wound healing. The thickness of the buccal alveolar bone, if present, was carefully measured at the time of tooth extraction using a calliper at 1 mm from the edge of the wall. The following clinical parameters were evaluated at baseline and after 4 months at implant placement: vertical bone changes, horizontal bone changes and width of keratinized gingiva. The length, diameter and need for additional bone augmentation were assessed for both groups at the time of implant insertion. Results The control group showed vertical bone resorption of 1 ± 0.7 mm, 2.1 ± 0.6 mm, 1 ± 0.8 mm and 2 ± 0.73 mm at the mesial, vestibular, distal and lingual sites respectively. Moreover, changes in horizontal dimension showed an average resorption of 3.6 ± 0.72 mm. The test sites showed a horizontal bone remodelling of 0.3 ± 0.76 mm, 1.1 ± 0.96 mm, 0.3 ± 0.85 mm, 0.9 ± 0.98 mm at the mesial, vestibular, distal and lingual sites respectively. The horizontal bone resorption at the test sites was 1.6 ± 0.55 mm. The keratinized gingiva showed a coronal shift of 0.7 mm in the control group when compared to 1.1 mm in the test group. In addition, 42% of sites in the control group required an additional bone augmentation at implant placement, when compared to 7% in the test sites. Conclusions This study clearly points out that an alveolar ridge preservation technique performed with collagenated porcine bone and a resorbable membrane – according to the procedure reported in this study – was able to limit the contour changes after tooth extraction. Finally, the test sites showed a better preservation of facial keratinized tissue when compared to control sites; grafted sites allowed the placement of longer and wider implants when compared to implants inserted in non‐grafted sites.